2014
DOI: 10.1037/a0035904
|View full text |Cite
|
Sign up to set email alerts
|

Determining the impact of prenatal tobacco exposure on self-regulation at 6 months.

Abstract: The goal of the present study was to examine the effects of maternal smoking during pregnancy on infant self-regulation, exploring birth weight as a mediator and sex as a moderator of risk. A prospective sample of 218 infants was assessed at 6 months of age. Infants completed a battery of tasks assessing working memory/inhibition, attention, and emotional reactivity and regulation. Propensity scores were used to statistically control for confounding risk factors associated with maternal smoking during pregnanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 68 publications
0
18
0
1
Order By: Relevance
“…Data for the present study were drawn from three waves of the MIDS, collected during pregnancy (28 weeks gestational age), and when children were 6 and 36 months old. MIDS is a predominantly low SES cohort (sample SES and demographic information is presented in Table ) prospectively recruited to study the effects of prenatal tobacco exposure on cognitive development (Espy et al, ; Wiebe et al, ; Wiebe, Fang, Johnson, James, & Espy, ). Mothers were recruited during pregnancy at two Midwestern study sites (Carbondale, Illinois, and Lincoln, Nebraska) and provided written, informed consent prior to their participation in the study.…”
Section: Methodsmentioning
confidence: 99%
“…Data for the present study were drawn from three waves of the MIDS, collected during pregnancy (28 weeks gestational age), and when children were 6 and 36 months old. MIDS is a predominantly low SES cohort (sample SES and demographic information is presented in Table ) prospectively recruited to study the effects of prenatal tobacco exposure on cognitive development (Espy et al, ; Wiebe et al, ; Wiebe, Fang, Johnson, James, & Espy, ). Mothers were recruited during pregnancy at two Midwestern study sites (Carbondale, Illinois, and Lincoln, Nebraska) and provided written, informed consent prior to their participation in the study.…”
Section: Methodsmentioning
confidence: 99%
“…As such, it makes sense to consider potential sex differences in vulnerability to PTE. There is some evidence that boys are more vulnerable: PTE's effect on birthweight is greater in boys than girls (Tayie & Powell, 2012), and sex has been found to moderate PTE's effects on attention and irritability in infancy (Pickett et al, 2008;Schuetze et al, 2008Schuetze et al, , 2013Willoughby et al, 2007; but for an exception, see Wiebe et al, 2014). Several studies have found that PTE is more strongly associated with externalizing behavior in boys, in independent samples assessed in early childhood and preadolescence (Hutchinson, Pickett, Green, & Wakschlag, 2010;Wakschlag & Hans, 2002).…”
Section: Sex Differences In Pte Vulnerabilitymentioning
confidence: 99%
“…There are certainly other quasi-experimental approaches (Rutter et al, 2001), such as Mendelian randomization (Wiebe, Fang, Johnson, James, & Espy, 2014) and natural experiments (e.g., across pregnancy; Class et al, 2014), as well as advances in the use of statistical covariates (e.g., propensity scores; West et al, 2014), that can help provide insight into causal mechanisms through which early risk factors influence later psychopathology because the approaches have different assumptions and limitations than those discussed here. We stress that the existing research using quasi-experimental designs as a whole clearly illustrates that such approaches are absolutely critical for studying early risk factors (Academy of Medical Sciences Working Group, 2007).…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…In this article, we reviewed several family‐based, quasi‐experimental designs and documented how research using these approaches has shed light on the DOHaD hypothesis as it relates to psychopathology. Other quasi‐experimental approaches that have different assumptions and limitations (Rutter et al., ), such as Mendelian randomization (Wiebe, Fang, Johnson, James, & Espy, ) and natural experiments (e.g., across pregnancy; Class et al., in press), along with advances in the use of statistical covariates (e.g., propensity scores; West et al., ) can also provide insight into causal mechanisms through which early risk factors influence later psychopathology. Research using quasi‐experimental designs has illustrated that such approaches are critical for studying early risk factors (Academy of Medical Sciences Working Group, ).…”
Section: Summary and Looking Aheadmentioning
confidence: 99%